Application of the SAW Method in a Decision Support System Recommendation for Poor Student Assistance Funds (BSM) at Budi Mulia Tumba Jae Private Junior High School - Damianus Daha; Paska Marto Hasugian (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
Assistance for Poor Students (BSM) is a National Program that aims to eliminate barriers for poor students to participate in school by helping poor students gain access to decent education services, prevent dropping out of school, attract poor students to return to school, help students meet their needs in learning activities, support Nine-Year Education Program (even up to high school), as well as helping the smooth running of school programs. Budi Mulia Tumbajae Private Junior High School is entrusted with allocating to the community through students with a quota determined by the District Education Office. At the Budi Mulia Tumba Jae Private Junior High School, the determination of prospective BSM fund recipients still uses a manual method, where each homeroom teacher registers the names of students from his class members who are considered underprivileged. The list of names is then submitted and selected at a meeting of the teacher and employee councils. This process allows for errors, fraud, subjectivity, and data manipulation. To facilitate the process of determining the prospective recipients of BSM funds, it is necessary to build a decision support system that can help provide recommendations for prospective recipients of BSM funds that are fast, flexible, and objective. In this study, the author uses the Simple Additive Weighting method which is often known as the weighted addition method. The basic concept of the Simple Additive Weighting method is to find the weighted sum of the performance ratings on each alternative and each attribute. The Simple Additive Weighting method requires the process of normalizing the decision matrix (x) to a scale that can be compared with all existing alternatives. By using the SAW method, the process of determining prospective BMS recipients is completed faster and the results are more accurate. It has been implemented by using the SAW method in Budi Mulia Tumba Jae Private Junior High School. The SPK application with the SAW method is the right choice to provide a good solution in determining the recommendations for prospective BSM recipients at Budi Mulia Tumba Jae Private Junior High School.